Preparation and characterization of ferromagnetic nickel oxide nanoparticles from three different precursors: application in drug delivery1. Issue 45 (20th May 2015) - Adhikary, Jaydeep; Chakraborty, Prateeti; Das, Balaram; Datta, Arnab; Dash, Sandeep Kumar; Roy, Somenath; Chen, Jeng-Wei; Chattopadhyay, Tanmay
<x xml:space="preserve">Abstract</x> Erythromycin conjugated NiO-NPs successfully deliver erythromycin to E. coli and S. aureus evidenced from MIC, MBC, DAD and drug uptake.